Attachment Style pada Individu yang Mengalami Shopping Addiction : Pendekatan Deskriptif Kuantitatif - Lifsha Zulvia (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
The phenomenon of shopping addiction has increasingly attracted attention in the field of psychology, alongside the rapid growth of technology and e-commerce. Shopping addiction is characterized by compulsive, impulsive, and repetitive buying behavior, even when individuals are aware of its negative consequences. This study aims to describe the attachment styles among individuals experiencing shopping addiction using a descriptive quantitative approach. The subjects consisted of 11 university students aged 18–21 years, selected through incidental sampling based on specific shopping addiction criteria. Data were collected using a questionnaire measuring attachment styles grounded in Bowlby’s and Ainsworth’s theories. The findings revealed that all subjects exhibited a secure attachment style. This result contrasts with previous theories suggesting that shopping addiction is more commonly associated with insecure attachment. The findings suggest that other factors, such as social conditions, personality traits, and environmental influences, may also contribute to the development of shopping addiction in individuals with secure attachment. This study offers new insights into the relationship between attachment styles and shopping addiction behavior among university students.